2012
DOI: 10.1523/jneurosci.3269-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

The Early Maturation of Visual Cortical Area MT is Dependent on Input from the Retinorecipient Medial Portion of the Inferior Pulvinar

Abstract: The hierarchical development of the primate visual cortex and associated streams remains somewhat of a mystery. While anatomical, physiological, and psychological studies have demonstrated the early maturation of the dorsal "where"/"how" or motion cortical stream, little is known about the circuitry responsible. The influence of the retinogeniculostriate pathway has been investigated, but little attention has been paid to the role of two more recently described disynaptic retinothalamic projections to the midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(132 citation statements)
references
References 56 publications
12
113
0
Order By: Relevance
“…Indeed, these pathways have been posited to underlie the ability of some of these patients to make unconscious ‘guesses’ about visual stimuli (blindsight) 24. Thus, where damage is specific to V1, any projections from the LGN or the pulvinar25 that may project to V2,26 V5/MT27 28 or other extrastriate regions may still be intact, and therefore OT fibres are preserved. As the lesion size is increased within the occipital lobe, the additional pathways are also affected, and therefore there is no longer a useful function for the OT.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these pathways have been posited to underlie the ability of some of these patients to make unconscious ‘guesses’ about visual stimuli (blindsight) 24. Thus, where damage is specific to V1, any projections from the LGN or the pulvinar25 that may project to V2,26 V5/MT27 28 or other extrastriate regions may still be intact, and therefore OT fibres are preserved. As the lesion size is increased within the occipital lobe, the additional pathways are also affected, and therefore there is no longer a useful function for the OT.…”
Section: Discussionmentioning
confidence: 99%
“…79,80 In fact, it recently was found that the early maturation of area MT likely is to be reliant on retinopulvinar input. 81 An alternative explanation is that OKR is less susceptible to response errors. Whatever the reason for the absolute difference between behavioral and OKR responses in adults, the close correlation between the two measures suggests that they target a common neural mechanism, which is likely to be global motion processing within the extrastriate visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The early connections through the pulvinar, shown in orange, have been suggested (e.g., Johnson, 2005; Warner, Kwan, & Bourne, 2012), although such links have not been demonstrated in human development. These links, colored in orange, are additions to earlier published versions of this figure (Atkinson, 2000; Atkinson & Braddick, 2012b).…”
Section: Introductionmentioning
confidence: 99%